On the hunt for improvements - Lithner, Jenny (2014)
The cheetah (Acinonyx jubatus) is one of the big feline species kept in zoos worldwide. The wild populations are quite small and therefore the captive population make up an important part of the total population of the world. Although life in the wild is not always easy and a captive environment provides shelter and food it does not come without problems. In captivity cheetahs become chronically ill and also develop stereotypic behaviours. Neither of these are problems in wild populations and both can be linked to stress in captivity. One mean of targeting stereotypic behaviour is to provide environmental enrichments. If it is targeted in the right way then it should reduce stress and may then also have an impact on disease development. The hunting behaviour of felids can be divided into main sequences of location, capturing, killing and processing of the prey. Since hunting behaviour is a natural behaviour often deprived from the animals in captivity I looked at possibilities of enrichments to stimulate this behaviour. Feasible enrichments could be feeding of carcasses or bones, live bait or a “cheetah run”. A cheetah run consists of a moving bait system giving the cheetah an opportunity to pursue lure. Enrichment through live bait or the cheetah run targets the sequences of location, capturing, and killing in the hunting behaviour, while the carcass-feed targets processing of the prey. The enrichments has positive effects on behavioural diversity and behaviour resembling of hunting has been observed in connection to the enrichments. However, the studies reviewed did not show any significant data on the reduction of stereotypic behaviour. No definite conclusions could be made but findings do suggest a feasibility to improve welfare through stimulation of hunting behaviour. More research is needed and targeting hunting behaviour might not be the most optimal choice, so therefore research need to also focus on evaluating enrichments in connection to other natural behaviours and conditions. Most research up to date focus on studying the effects on one factor e.g. corticoids concentration or stereotypical behaviour. These factors are not reliable on their own and research therefore needs to investigate several factors simultaneously to make more accurate predictions on how welfare is affected. More accurate predictions will lead to clearer guidelines and thereby efforts of improvement can be directed towards areas were most effect will be seen.